Does competitive position matter: Investigating the impact of information risk on COE and corporate investment - Sana Saleem; Muhammad Usman; Muhammad Naveed Akhtar (PLoS ONE, 2025)
Purpose The purpose of this study is to find out how firm’s competitive position plays the moderating role between the relation of information risk and COE. The study considers the effect of two different types of information risk, i.e., lack of information quality and transparent information. Methodology The data of the study is collected from all the non-financial firms listed on PSX from 2007 to 2022. Two-step system GMM dynamic panel estimators are applied to test the dynamic nature of the proposed model. Findings/Results The findings show that firms having better competitive position signal their strength through improved information disclosure in order to gain the confidence of shareholders. This competitive environment poses a governance effect by imposing discipline on manager’s behavior, reducing information asymmetry and improving the quality of information disclosure, resulting in reduction of the COE. Further, a more competitive environment improves the readability of the annual report and reduces information asymmetry. In addition, by reducing financing frictions, this research provides new and unique insights pertaining to the importance of competitive position in the sensitivity of investment to information risk. Originality This research extends to the corpus of literature by investigating the unexplored strategic determinants, such as a firm’s competitive position, to mitigate the impact of two distinct types of information risk: lower quality and reduced transparency. Additionally, it explores how these risks influence both the cost of equity and corporate investment.